Information and communication technologies in the feeling of happiness and self-esteem of pre and post retirement - Carmo, Elisangela Gisele do; Silva, Renata Laudares; Fukushima, Raiana Lídice Mór; Venâncio, Reisa Cristiane de Paula; Micali, Pollyanna Natalia; Costa, José Luiz Riani; Schwartz, Gisele Maria (Revista Hipótese, 2018)
This qualitative study, analyzes the use of Information and Communication Technologies (ICT) and the influence on the feelings of happiness and self-esteem of 20 pre and 20 post-retired. Through a structured interview, the results emphasizes the importance of ICT to provide sensations of pleasure, Well-being, happiness, self-esteem and belonging, implying in parallel efforts for the socialization of the individual.
Keywords: Information and Communication Technologies; Happiness; Self esteem; Retirement